Identidade e epistemologia narrativa - Souza, Rafael Britto de (2008)
This dissertation begins with the premise that the Narrative Psychology paradigm opens new and promising perspectives to the study of Psychology in general. Our work aims to enumerate logical, epistemological and psychological arguments that can back this premise up. Methodologically this research is divided in two sections. In the first one, we investigate the epistemological ground of this paradigm. The relation with both the post-foundationalist approach and the analytic philosophy of ordinary language is disclosed. We defend also that the narrative concept has much to gain when it is read as a language game, among a myriad of others. In the second chapter we intended to exemplify the advantage of this approach over other traditional ways to treat the problem of psychological identity. Given its complexity, the concept of narrative identity has to be treated in at least three levels, comprising three great groups of questions. These questions are: the persistence of identity along time, the question of the unity and the question of substance. The use of narrative concept showed to be, at the same time, a simple and a broad way to solve the problems raised by these questions. Such a result points to a sample of the benefits that can be reaped from the adoption of this paradigm.